Preparing ideal mix of spices - Mumbai Archive Project Team (Jio Institute, 2024)
Preparing the ideal mix requires patience, training, and skill. The skill of the making lies in accurately measuring the right proportion of each spice, which can affect the pungency and heat of the blend.